2021
DOI: 10.1007/s11604-021-01204-7
|View full text |Cite
|
Sign up to set email alerts
|

Bowel habits and gender correlate with colon length measured by CT colonography

Abstract: Purpose CT colonography enables three-dimensional measurement of colon length. However, previous studies using CT colonography have not examined the association with gender, age, physique, a history of laparotomy and bowel habits, all possible contributory factors to colon length. The aim of this study is to investigate factors associated with colon length. Materials and methods We conducted a post hoc analysis based on data obtained from a previous multi-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 29 publications
1
6
0
Order By: Relevance
“…The colon in females was longer than in males in keeping with previous findings [ 19 ]. The reasons for this difference are unclear but could include hormonal and/or gynecological factors [ 19 ].…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…The colon in females was longer than in males in keeping with previous findings [ 19 ]. The reasons for this difference are unclear but could include hormonal and/or gynecological factors [ 19 ].…”
Section: Discussionsupporting
confidence: 92%
“…This illustrates that the organ volume changes shown in [ 12 ] are actually reflected in elongation which, in turn, may affect longitudinal muscle physiology. Colon elongation, affecting the longitudinal muscles, may be secondary as a result of fecal impaction [ 19 ], though it is difficult to dissect whether colonic elongation might be a primary factor in constipation [ 17 ]. The colon in females was longer than in males in keeping with previous findings [ 19 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Intestinal morphology is important for both endoscopic and radiological diagnostic procedures and conservative and surgical treatment (Bunni 2022; Kapadia 2017; Utano et al, 2021). There are at least three modern and very popular diagnostic tools – colonoscopy, capsule endoscopy and computed tomography colonography (so‐called virtual colonoscopy).…”
Section: Discussion and Proposal For Simplificationmentioning
confidence: 99%
“…We supported the observations of other authors (Madiba et al 2008 ; Raahave 2018 ; Bourgouin et al 2012 ), which are important for different diseases or pathological bowel conditions. Utano et al (321 patients studied with CT colonography) analyzed colon length in relation to gender and bowel habits (constipation) and found that total colon length was greater in women with constipation (infrequent bowel movements) (Utano et al 2021 ). The same factors related to bowel anatomy are also important in diagnostic procedures, including colonoscopy or capsule endoscopy.…”
Section: Discussionmentioning
confidence: 99%